Design of freeform lens for WLEDs on the fishing boat - Nguyen Thi Phuong Loan; Thinh Cong Tran (Universitas Ahmad Dahlan, 2020)
In this article, a free secondary lens is designed for an LED fishing/working lamp (LFWL), which is recommended for the purpose of taking the place of a traditional high-intensity discharge (HID) fishing lamp. To serve the lighting needs of fishing and the on-board activities on fishing boats, the innovative LED lamp is proposed. To make the freeform lens in our optics design process, we depended on Gaussian decomposition. In this way, it is easy to approach the targeted light intensity distribution curve (LIDC) of the LFWL lens. The simulated results show that the performance of the LED fishing/working lamps is much better than that of HID fishing lamps for illumination onboard, on the sea-surface, and underwater. Meanwhile, a lighting efficiency of 91% with the power consumption reduction of more than 50% can be achieved when the proposed LED fishing/working lamps are used instead of the HID fishing lamps.